1, 2-Bis(diphenylphosphino)ethane nickel(ii) O, O′-dialkyldithiophosphates as potential precursors for nickel sulfides. (17th January 2017) - Yadav, Reena; Singh, Ashish Kumar; Waghadkar, Yogesh; Kociok-Köhn, Gabriele; Kumar, Abhinav; Chauhan, Ratna; Rane, Sunit; Gosavi, Suresh
Abstract : Three new dppe nickel(ii ) dithiophosphates with different counteranions synthesized and decomposed to obtain Ni–S systems with same phase independent of the nature of counteranions and alkyl fragments. Abstract : In this work, three heteroleptic Ni(ii )dppe dithiophosphate complexes, [Ni{S2 P(OC2 H5 )2 }(dppe)]B(C6 H5 )4 (1 ), [Ni{S2 P(OCH(CH3 )2 )2 }(dppe)]PF6 (2 ) and [Ni{S2 P(OCH(CH3 )2 )2 }(dppe)]B(C6 H5 )4 (3 ) (dppe=1, 2-bis(diphenylphosphino)ethane), have been synthesized and characterized by analytical and spectroscopic techniques (microanalysis, IR, UV-Vis, 1 H, 13 C and 31 P NMR spectroscopy) as well as single crystal X-ray crystallography. The crystal structures of all complexes displayed a distorted square planar geometry around the Ni(ii ) center bonded through two sulfur atoms of the dithiophosphate ligand and two phosphorus atoms of dppe. The TGA results indicated that all three compounds display loss of solvents at the outset and decompose to Ni–S phase systems and hence may act as potential precursors for nickel sulfides. Investigations indicated that the bulkiness of counteranions as well as the alkyl fragment of the dithiophosphate ligands do not have any effect on the morphologies of as-synthesized nickel sulfides.